2011
DOI: 10.1016/j.ejca.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Altered CD94/NKG2A and perforin expression reduce the cytotoxic activity in malignant pleural effusions

Abstract: This study was aimed at assessing whether cytotoxic lymphocytes (CD8+) and NK cells from malignant pleural effusions have a deregulated expression of CD94/NKG2A.The expression of membrane CD94/NKG2A and perforin was evaluated by flow-cytometry in CD8+ and NK cells from pleural effusions and autologous peripheral blood of cancer (n = 19) and congestive heart failure (CHF) (n = 11) patients. Intracellular CD94/NKG2A expression was evaluated by flow-cytometry in pleural effusion CD8+ and NK cells from cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Interestingly, we found that a high density of CD8+ IEL‐TIL was associated with an improved DFS, as already reported in previous studies 32–35. In fact, our results extend and deepen these previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, we found that a high density of CD8+ IEL‐TIL was associated with an improved DFS, as already reported in previous studies 32–35. In fact, our results extend and deepen these previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…Relative to this, MPE is characterised by defective recruitment, activation and the cytotoxic potential of CD8 + cells [22,23]. Macrophages from malignant effusions not only display reduced cytotoxic activity against autologous tumour cells but they also inhibit tumour cell apoptosis [24,25].…”
Section: Pathophysiology Of Mpementioning
confidence: 99%
“…TIGIT was reported to decrease NK cell-mediated killing of CD155-expressing cells in both humans and mice [14, 29, 30]. As reported in several articles, the expression of inhibitory receptors, such NKG2A [31] and KIR3DL1 [21], on NK cells usually increases in different cancers. However, in this study, we did not find differences between TIGIT expression in PC patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%